Democracy works turning politics to Africa's advantage - Mill, Greg. (London Hurst and Company, 2019)
Democracy Works asks how we can learn to nurture, deepen and consolidate democracy in Africa. By analyzing transitions within and beyond the continent, the authors identify a 'democratic playbook' robust enough to withstand threats to free and fair elections. However, substantive democracy demands more than just regular polls. It is fundamentally about the inner workings of institutions, the rule of law, separation of powers, checks and balances, and leadership in government and civil society. It is also about values and the welfare and well-being of its citizens, and demands local leadership with a plan for the country beyond simply winning the popular vote.
Includesx index
Keywords: Democracy